Periodontal treatment effects on endothelial function and cardiovascular disease biomarkers in subjects with chronic periodontitis: protocol for a randomized clinical trial. (2011)
Background Periodontal disease (PD) is an infectious clinical entity characterized by the destruction of supporting tissues of the teeth as the result of a chronic inflammatory response in a susceptible host. It has been proposed that PD as subclinical infection may contribute to the etiology and to the pathogenesis of several systemic diseases including Atherosclerosis. A number of epidemiological studies link periodontal disease/edentulism as independent risk factor for acute myocardial infarction, peripheral vascular disease, and cerebrovascular disease. Moreover, new randomized controlled clinical trials have shown an improvement on cardiovascular surrogate markers (endothelial function, sICAM, hsPCR level, fibrinogen) after periodontal treatment. Nonetheless, such trials are still limited in terms of external validity, periodontal treatment strategies, CONSORT-based design and results consistency/extrapolation. The current study is designed to evaluate if periodontal treatment with scaling and root planning plus local delivered chlorhexidine improves endothelial function and other biomarkers of cardiovascular disease in subjects with moderate to severe periodontitis.